Surgical treatment of pelvic chondrosarcoma. An outcome analysis of 12 cases - Sharifudin, Mohd Ariff; Wan Ismail, Wan Faisham Numan; Wan, Zulmi; Mat Zin, Nor Azman; Mohamed Amin, Mohamed Azril; Goh, Kian Liang (2014)
Introduction: Chondrosarcoma is a primary malignant skeletal tumour from cartilaginous differentiation. Surgical resection is the only available treatment in achieving an oncologic clearance since the other adjuvant treatments are ineffective. It is more challenging when the tumour arises from the pelvis. Methodology: Cases of pelvic chondrosarcoma underwent surgical resection with or without reconstruction in a single tumour centre in the past decade were reviewed. Results: There were 6 males and 7 females with a mean age of 42.8 years (range 18 to 59). 3 had lesions in the ilium and 4 in the periacetabulum. Ischiopubis, sacrum, and involvement of the whole hemipelvis had 2 cases each. Limb salvage was performed in 11 patients and amputation in 2. 2 cases required hindquarter amputation after 2 years following the first surgery due to local recurrence or chronic infection. All patients except with multiple distant metastases underwent surgery with curative intentions. 70% of cases in the limb salvage group had positive microscopic margins compared to a single case in the amputation group. Local or pedicled flap were required for wound coverage following hindquarter amputation. 2 limb salvage cases required pedicled flap for soft tissue reconstruction following resection of ischiopubic tumours. The average follow-up was 103 months. 10 cases were still alive on their last follow up; 8 being disease-free and 2 had local recurrence. 10 cases were complicated with infections. Sciatic nerve injuries were seen in 2 cases. Majority had fair functional outcome on their last follow up but amputees had poor functional outcomes. Conclusion: Favorable oncologic and functional outcomes can be achieved with limb salvage procedures in selected patients. Complication rates were high; however, facing the aim of limb salvage as well as poor functional outcomes following amputation, a certain number of complications is acceptable.